2021
DOI: 10.1016/j.msard.2021.103251
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response following SARS-CoV-2 mRNA vaccination concomitant to anti-CD20 therapy in multiple sclerosis

Abstract: Background : The immunogenicity of COVID-19 vaccine among patients receiving anti-CD20 monoclonal antibody (Ab) treatment has not been fully investigated. Detectable levels of SARS-CoV-2 immunoglobulin G (IgG) are believed to have a predictive value for immune protection against COVID-19 and is currently a surrogate indicator for vaccine efficacy. Objective : To determine IgG Abs in anti-CD20 treated patients with multiple sclerosis (MS). Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 34 publications
0
26
0
1
Order By: Relevance
“…Among them, 52 studies fulfilled the criteria for the present meta-analysis: 30 investigated lymphoid malignancies 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ; and 22 investigated anti-CD20 antibody therapy for non-malignant diseases, such as multiple sclerosis and rheumatic diseases. 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 28 articles were excluded with the following reasons: (1) insufficient data of outcomes, 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 (2) duplicate publications from an overlapping cohort, 97 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 52 studies fulfilled the criteria for the present meta-analysis: 30 investigated lymphoid malignancies 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ; and 22 investigated anti-CD20 antibody therapy for non-malignant diseases, such as multiple sclerosis and rheumatic diseases. 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 28 articles were excluded with the following reasons: (1) insufficient data of outcomes, 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 (2) duplicate publications from an overlapping cohort, 97 ...…”
Section: Resultsmentioning
confidence: 99%
“…6 B). Treatments within the past 6 months, 67 , 68 , 69 , 70 , 74 , 77 , 78 , 79 , 80 , 83 , 84 , 86 9 months, 67 , 68 , 74 , 78 , 87 and 12 months 68 , 77 , 84 , 85 , 87 were all associated with significantly decreased seropositivity rates compared with treatment > 6, 9, and 12 months before vaccination, respectively (within 6 months, RR 0.45 [95% CI 0.35–0.57]; within 9 months, RR 0.54 [95% CI 0.34–0.84]; within 12 months, RR 0.49 [95% CI 0.33–0.73]) ( Fig. 6 C- 6 E).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, if clinically justifiable, extending the infusion interval between anti-CD20 antibody infusions and/or between the vaccine doses should be considered to increase the chances of successful vaccination against SARS-CoV-2 [30]. However, it is currently unclear how long the subsequent administration of CD 20 depleting therapies should be postponed, as a recently published study found no positive effect after an interval of up to 43 weeks in 60 RRMS patients vaccinated with mRNA vaccines [31]. There is emerging evidence in pwMS that the extent of vaccine-induced humoral responses correlates better with the extent of B-cell reconstitution at the time of vaccination than with the time window between the last anti-CD20 infusion and vaccination [32].…”
Section: Discussionmentioning
confidence: 99%
“…Guerrieri, et al, found a marked attenuation with OCR (only 37.5% of patients had a response) whereas FTY had a more robust response (62.5%) ( Guerrieri et al, 2021 ). Novak, et al, found a decreased humoral response to OCR ( Novak et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%